RANCANG BANGUN SISTEM PENGADUAN LAYANAN AKADEMIK STMIK STIKOM INDONESIA - suryawan, I Gede Totok; Handika, I Putu Susila (LPPM STMIK STIKOM Indonesia, 2018)
This paper discusses the design of academic service complaints system in STMIK STIKOM Indonesia. Currently, the evaluation of academic services at STMIK STIKOM Indonesia has been done periodically in the form of distributing questionnaires to the students before taking the final exam of Semester (UAS) in each semester. This evaluation is quite effective but this periodic evaluation can not yet accommodate the academic service complaints that occur in the everyday incident. In this paper has developed a system of web-based academic service complaints that can be accessed at any time by the academic community to provide feedback related to academic services at STMIK STIKOM Indonesia. In general, the system is capable of managing user data such as students, lecturers, institutions, and administrators. The system is able to make a complaint file to be sent to service provider units within the academic community, and the files sent will be accessed through the